Simulation of the Charge Motion near the Velocity of Light in Electric and Magnetic Fields - Morooka, Masami (Transactions on Engineering and Computing Sciences, 2015)
A numerical simulation method for the charge motion near the velocity of light in electric and magnetic fields has been investigated using the relativistic mass by Einstein’s special theory of relativity, and an electron acceleration for the Larmor motion in a static magnetic field perpendicularly applied a synchronized alternative electric field has been simulated by Java programing. The simulation results in a limitation of the electron velocity to a considerably lower value than the velocity of light in contradiction to the previous simulation in which the electron is easily accelerated over the velocity of light due to the use of the invariant mass.